Radiographic evaluation of the margins of clinically acceptable metal-ceramic crowns - Sheikh Bilal Badar; Kamil Zafar; Robia Ghafoor; Farhan Raza Khan (Journal of the Pakistan Medical Association, 2022)
Objective: To radiographically evaluate the proximal marginal fit of the clinically acceptable metal-ceramic crowns. Method: The prospective study was conducted at the dental clinics of Aga Khan University, Karachi, from July to December 2018, and comprised metal-ceramic crowns that were evaluated prior to the cementation. Clinical examinations were conducted by seating the crown on the tooth preparation and visual assessment was done using sharp explorer along the margins. Clinically acceptable crowns were then evaluated on the bite-wing radiograph. Any horizontal or vertical inaccuracy of >0.5mm at the proximal margins was recorded as ’discrepancy’. Data was analysed using SPSS 22. Results: Of the 230 interproximal margins of 115 crowns evaluated, 113(49.1%) sites had marginal discrepancies; 44(19.1%) horizontal discrepancies, 58(25.2%) vertical discrepancies, and 11(4.8%) having both horizontal and vertical discrepancies. Horizontal crown margin discrepancies were most associated with the mesial site of the maxillary crowns, while vertical discrepancies were commonly associated with the distal aspect of all crowns (p<0.050). Conclusions: Almost half of the crowns that were considered clinically acceptable had some vertical or horizontal marginal discrepancy on radiographic evaluation. Continuous...